"When does it stop? Does it ever stop?" - the business of being a guy: men and masculinities in Carol Shields's novels - Camastra, Małgorzata Maria (2014)
This thesis focuses on the portrayal of men and masculinities in Carol Shields’s novels. There is a conspicuous gap in the scholarly research on Shields's oeuvre which significantly sidelines her male characters. The focus of academic interest often falls on the author's engagement with feminism, almost solely concentrating on her female protagonists. Along with new developments in masculinity studies I give prominent attention to men in Shields's novels to illustrate how the feminist standpoint is filtered through masculine perspectives. The aim of this thesis is to show how the presentation of male characters in Carol Shields’s novels refracts wider societal changes and evolving theoretical paradigms of masculinity, and to trace how these portrayals evolve as a consequence of social developments. The thesis also stresses how Shields's novels become increasingly experimental, partially embracing postmodern ideas and techniques and combining them with questions about the position and situation of women and men in society. Only by reading male and female characters together, the thesis argues, are we able to build a holistic picture of Shields's literary achievement. Even though, on the surface, Shields's narratives feature most average male characters – white, middle-class, heterosexual North Americans – the protagonists and their constructions vary considerably from one narrative to another. Shields published her first novel in 1976 and her last in 2002. Thirty years of her writing career coincide with a turbulent period in the social life of the Western hemisphere. The emphasis of this thesis is on how Shields’s novels engage with the changing intellectual environment of second- and third-wave feminism, masculinity studies and postmodernism. Construction of gender in the novels changes: it becomes much more complex, less defined and more open to (re)interpretation. In novels such as Swann, The Republic of Love or The Stone Diaries we witness the emergence of postmodern masculinity which is fragmented, self-questioning and unstable. Men’s stories become increasingly complex as filtered through numerous layers of narrators’ and focalisers’ lenses. Also male characters gain more potential as protagonists achieve the capacity to reinvent themselves and their stories. However, as depicted in the novels, a postmodern man still occupies a dominant social position over women and still blames his mother for his failures in adult life, in spite of socio-political changes. As such Shields’s works express great sadness and disillusionment with feminism’s failure to allow women to assume equal status with men; however, the texts never blame men openly for social imbalance. Rather, Shields’s protagonists are united in their inability to control their stories and it is the social system that oppresses and limits women and men. Finally, the thesis shows the author's great skill and deep engagement in revealing the workings of the twentieth-century North American culture which reshapes definitions of what a man and what a woman is at a given time in history. Shields’s novels uncover and expose the mechanisms behind such artificial and arbitrary constructions which are often blindly accepted as the only true norm.